Republic of Kosovo : 2011 Article IV Consultation and the Initiation of a Staff-Monitored Program: Staff Report; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Kosovo is still in the process of building key social and economic institutions. Economic performance over the past decade has been robust, but growth has been tilted toward domestic demand, fuelled by transfers and non-debt creating capital inflows. The adoption of the euro provides a strong monetary anchor, but it increases the demands on macroeconomic management. Further progress in Kosovo's banking system is impeded by limited legal capacity and incompletely defined property rights. The short-term macroeconomic outlook is benign, even though there are significant downside risks.